Integrating socioscientific issues and model-based learning to decide on a local issue: the white butterfly unit. (3rd April 2023) - Durak, Benzegul; Topçu, Mustafa Sami
Abstract: Recent research suggests that integrating model-based learning and socioscientific issue based instruction helps students construct meaningful learning in science classrooms. Thus, this paper presents a unit plan that integrates model-based learning and socioscientific issues. The focus of the unit is the white butterfly which is a local pest. A 4-week middle school unit was developed on the driving question, "How might the population change of the white butterflies interact with the local ecosystems?". Evaluation of the unit was made through students' models and explanations. There were three modeling sessions throughout the unit. "Components" and "Explanatory Process" rubrics were developed to evaluate the models and explanations. The results showed that students' pre-knowledge about the white butterfly and its relationship with the local ecosystem was quite limited and throughout the lessons they were questioned and gained knowledge about the relationship between the white butterfly and ecosystem. Also, students became able to explain the effects and results of the methods used to control the white butterfly but not able to show them by drawing. Therefore, it is highly recommended to evaluate the models together with their explanations, as students' drawing skills are a limitation for the use of models.